Statues and the Emergence of Dalit Visual Field in Southern Kerala - R, Rajeev (Integrated Journal for Research in Arts and Humanities, 2024)
Kerala has over 32,000 colonies, of which 8,000 are Dalit colonies, known for their marginalisation and harsh living conditions. Every other elected government in Kerala supports the caste colonies, a physical manifestation of the institutionalised caste system that continues to marginalise communities under the guise of progress. Post-colonial Dalit politics in Kerala evokes memories of these communities, with images of historical heroes emerging with unequal significance. Concrete statues, often depicting historical icons and leaders, pay homage to prominent figures like Ayyankali, who championed the cause of Dalit rights. These statues serve as reminders of their contributions to the ongoing discourse against discrimination, acting as catalysts for community empowerment and the nurturing of a strong Dalit identity. The aim of this paper is to examine how concrete statues started to emerge as a new trend of Dalit assertion in these colonies as well as in the post-colonial visual field in Kerala. It also inquires how, by becoming the focal points for community gatherings, celebrations, and discussions on social issues, the statues inspired pride, unity, and collective action within the Dalit community.